Fusarium proliferatum, a New Pathogen Causing Head Blight on Oat in Argentina - Stenglein, Sebastián (2010)
Oat (Avena sativaL.) is widely grown (~200,000 ha) for livestock feed in Argentina.Fusariumspp. affect yield and commercial quality and can cause indirect losses because someFusariumspp. produce mycotoxins. In December 2008, a study of oat seeds (cv. Graciela INTA) from Trenque Lauquen, Buenos Aires, Argentina was conducted. Seeds (400) were surface sterilized by dipping successively into 70% ethanol for 2 min, 5% sodium hypochlorite for 2 min, rinsed twice in fresh sterilized distilled water, plated on 2% potato dextrose agar (PDA) pH 6, and incubated at 24 ± 2°C with 12-h photoperiods. Six isolates morphologically similar toFusariumspp. were observed after 6 days of incubation. For identification, monosporic isolates were transferred onto 2% PDA and carnation leaf agar (CLA) to grow with the conditions described above. Two isolates produced abundant, white, aerial mycelium and violet-to-dark (with age) pigments in the PDA. On CLA, macroconidia were abundant, slender, almost straight, thin walled, and usually three to five septate. Microconidia were abundant, usually single celled, oval or club-shaped in chains (less commonly in false heads) on monophialides and polyphialides. Chlamydospores were absent. The fungus was identified asFusarium proliferatum(Matsushima) Nirenberg on the basis of fungal morphology (1). To complete Koch's postulates, the pathogenicity of the fungus was tested by spraying five healthy inflorescences of oat (cv. Graciela INTA) with a 5-ml suspension (2 × 105conidia/ml). Another two healthy inflorescences were sprayed with sterile distilled water. Plants were placed in a growth chamber with a 12-h photoperiod at 22 ± 2°C and covered with polyethylene bags that were removed after 3 days and plants were moved to a glasshouse. This procedure was repeated. While control inflorescences were asymptomatic, inoculated inflorescences showed bleaching glumes that sometimes became necrotic with some grains that presented pale brown discoloration and necrotic areas. The fungus was reisolated from glumes and grains of inoculated plants and not from controls using the methodology described above. To confirm the morphological diagnosis, the genomic DNA of the isolates was extracted (3) and a PCR reaction with specific primers 5′-CTTTCCGCCAAGTTTCTTC-3′-forward and 5′-TGTCAGTAACTCGACGTTGTTG-3′-reverse was chosen (2) using the following cycling protocol: initial denaturation step at 95°C for 2 min; 30 cycles at 95°C for 30 s, 55°C for 30 s, 72°C for 45 s; final extension at 72°C for 2 min. Successful amplifications were confirmed by gel electrophoresis. Size of the DNA fragment was estimated using a 100-bp DNA ladder. The reaction was repeated three times. The expected size product (585 bp) was obtained, confirming the identification (2). To our knowledge, this is the first report ofF. proliferatumon oat in Argentina. This species is known to produce fumonisins, beauvericin, fusaric acid, fusarins, and moniliformin toxins, among others. SinceF. proliferatumcan infect different cereal grains, a large-scale survey in the same and different fields is in progress. A voucher culture has been deposited in the LPSC (Culture Collection of the La Plata Spegazzini Institute) No. 1058.